Interactive Learning Using E-Learning Module in Learning English for Senior High School: A Review of Related Articles - Dewi, Yosa Novia; Zaim, Muhammad; Rozimela, Yenni (Journal of Education, Language Innovation, and Applied Linguistics, 2022)
Technological advances affect people’s working lives and contribute to the education system, especially in the learning process for generation 4.0. Generation 4.0 is a generation that is fully exposed to technological developments even from birth, so learning using technology will have a very good effect on them. However, conventional learning in schools is still dominated by conventional learning that uses textbooks as teaching media. Therefore, this study was conducted to determine the benefits of implementing interactive learning using the E-Learning Module. The data was collected through a review of international journals starting from 2015 to 2019. The findings show that one of the appropriate media used to teach the current 4.0 generation is interactive learning or known as learning, which uses interactive multimedia with interesting materials to motivate students to learn when and anywhere. This study also found that learning using the interactive learning module has advantages in pedagogical aspects such as collaborative learning, mixed learning, interactive learning, experiential learning, and problem-based learning. Keywords: E-learning; Interactive Learning Module; Multimedia; Motivation; and Generation 4.0.